A Promising Anticancer Agent Dimethoxycurcumin: Aspects of Pharmacokinetics, Efficacy, Mechanism, and Nanoformulation for Drug Delivery - Sohail, Muhammad; Guo, Wenna; Yang, Xin; Li, Zhiyong; Li, Yanli; Xu, Hui; Zhao, Feng (Frontiers in Pharmacology, 2021)
Curcumin is a well-known anti-cancer natural product with various significant bioactivities that has been well documented, but its widespread use is far mainly hindered by insufficient ADME properties such as poor solubility and low metabolic stability. Dimethoxycurcumin (DiMC) is a kind of lipophilic compound derived from curcumin that maintains its anti-cancer potency and has greatly improved systematic bioavailability. Therefore, DiMC is regarded as a promising plant-derived anti-cancer agent deserved to be well developed. Herein we concentrate on the published work by those from original research groups concerning with pharmacokinetics, efficacy and mechanism of DiMC involved in the treatment of various tumors, as well as the nanoformulations for effective drug delivery.